Recent Advances in Molecular diagnosis curbing the COVID-19. (August 2020) - Aziz, Hafsa; Fatima, Shazia; Iqbal, Huma; Faheem, Mohammad
Highlights: FDA has approved number of molecular tests for emergency use to address the pandemic confronting the world. Broad testing will help to identify infected person, enabling proper quarantining, treatment and control. No comparative analytical information is available about tests approved for emergency use. This is a summary of FDA emergency use authorization(EUA) recommended nucleic acid diagnostic modalities.